EFEKTIFITAS LEVEL INKUIRI PADA PEMBELAJARAN STOIKIOMETRI UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KEMAMPUAN ALGORITMA MAHASISWA - Fahyuddin Fahyuddin; Abraham Rahman (Halu Oleo University, 2022)
This study aims to examine the effectiveness of two levels of inquiry in increasing students' conceptual understanding and algorithmic abilities in solving stoichiometry problems. The levels of inquiry that were examined for their effectiveness on direct instruction were structured inquiry and guided inquiry. The sample of this study consisted of 96 chemistry education students who attended basic chemistry courses which were distributed in three parallel classes with the same characteristics, such as age and initial knowledge. This research is a quasi-experimental study using a pretest-posttest control group design. Two classes were randomly selected to receive structured inquiry learning and guided inquiry, while one other class received direct instruction (DI). The results showed that the increase in students' understanding of stoichiometry concepts did not differ significantly between the levels of inquiry and DI. The structured and guided inquiry levels did not differ significantly in increasing understanding of stoichiometry concepts. Another finding in the study was that the algorithmic abilities of students who received structured inquiry learning were significantly better than the student groups in the other two study groups, while the results of guided inquiry learning were not different from those of direct instruction.